Value Proposition Design Of Luxury Class Sleeper Rail Bussiness Units - Rachmawati, Indira; Mayyu, Aulia Nisa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The purpose of this research is to understand the needs and desires of customers, including their perceptions and expectations, regarding the luxury sleeper train operated by PT Kereta Api Indonesia. The data analysis technique employed is the value proposition design using a descriptive qualitative research method. The value proposition design is used to specifically identify target customers based on problem definition, needs, desires, and what customers should avoid. The outcome of this research is a value proposition design that consists of customer jobs, customer pains, and customer gains from the luxury sleeper train segment of PT Kereta Api Indonesia's customers.